2015
DOI: 10.1093/cid/civ171
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Timing of Initiation of Antiretroviral Therapy During Primary HIV-1 Infection on the Decay of Cell-Associated HIV-DNA

Abstract: This study provides strong arguments in favor of cART initiation at the earliest possible time point after HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
104
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 35 publications
12
104
2
Order By: Relevance
“…Jain et al (27) showed that early ART (within 6 months of infection) was associated with lower levels of cell-associated HIV DNA and RNA as well as lower levels of CD4 and CD8 T-cell activation. Again, the authors suggested timing of ART to be a critical determinant of reservoir size, consistent with prior studies (11,14,15,(28)(29)(30).…”
Section: Discussionsupporting
confidence: 82%
“…Jain et al (27) showed that early ART (within 6 months of infection) was associated with lower levels of cell-associated HIV DNA and RNA as well as lower levels of CD4 and CD8 T-cell activation. Again, the authors suggested timing of ART to be a critical determinant of reservoir size, consistent with prior studies (11,14,15,(28)(29)(30).…”
Section: Discussionsupporting
confidence: 82%
“…Failure of HIV DNA to decrease in 12 months post-cART in pTfh and non-pTfh cells of chronically infected patients is not surprising. It is well known that the rate of decay of cell-associated HIV DNA is fastest in patients initiating treatment very early during the acute infection, and even in these situations the decay can take up to 8 months following cART initiation (44)(45)(46). In our study, all patients were chronically HIV infected, and it is likely that HIV DNA decay takes longer than 48 weeks on cART.…”
Section: Discussionmentioning
confidence: 67%
“…In our study, all patients were chronically HIV infected, and it is likely that HIV DNA decay takes longer than 48 weeks on cART. The fast firstphase decay of viral DNA could result from the clearance of activated and productively infected T EM and T TM CD4 T cells (47) rather than the less activated long-living T CM cells (46,47). Further, T EM and T TM CD4 T cells have shorter half-lives and are infected earlier than naive and T CM cells due to their higher level of immune activation and coreceptor expression.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches include boosting HIV-specific immunity, reducing inflammation, activating latency, and targeting HIV apoptosis regulatory pathways. 7,[31][32][33] Recent studies also point out that ART initiated during early AHI either prevents loss of (at Fiebig stage I/II) or restores (at Fiebig stage III) mucosal Th17 cells. 34 Consequently, very early ART is associated with normalization of local and systemic immune activation, reversing a hallmark of HIV pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…6 This seronegative window is thus of crucial importance for early treatment outcome, vaccine development, and public health. 7,8 Despite the importance of AHI, there are immense difficulties identifying AHI patients for treatment initiation. Patients are often asymptomatic or experience a nonspecific febrile illness; a diagnostic dilemma compounded in the African setting by a significant symptom overlap with malaria.…”
Section: Introductionmentioning
confidence: 99%